Performance of Napier and Guinea Grasses under Rain-Fed Conditions in Foot Hills of Doon Valley - Singh, Charan; Singh, Rambir; Gulati, Ajay (Indian Forester, 2016)
Napier (Pennisetum perpureum Scumach) and Guinea (Panicum maximum Jacq.) grasses are considered as good palatable fodder for cattle. These grasses are grown under silvi-pastoral systems in our country. In state of Uttarakhand, farmers have a lot of rain-fed area that may be used for development of silvopastoral systems to meet demand and supply of green fodder. Keeping in view, an experiment was set up on degraded land at Kharakhet, a village in tehsil Vikas Nagar and district Dehradun of Uttarakhand to find out the performance of hybrid Napier (CO-3) and Guinea grass. On observation, it was found that survival percentage and sprouting capacity on sandy loam and slightly acidic degraded land was better in the hybrid Napier grass with average survival percentage of 83.80±6.30 and sprouting capacity of 11.40±1.67 per slips. On the other hand, Guinea grass showed poor performance with 12.20±4.27% survival and sprouting capacity of 5.20±0.83 per slip.